2011
DOI: 10.5194/hess-15-1291-2011
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of eddy-covariance and large aperture scintillometer measurements with respect to the energy balance closure problem

Abstract: Abstract.We analyzed the seasonal variations of energy balance components over three different surfaces: irrigated cropland (Yingke, YK), alpine meadow (A'rou, AR), and spruce forest (Guantan, GT). The energy balance components were measured using eddy covariance (EC) systems and a large aperture scintillometer (LAS) in the Heihe River Basin, China, in 2008 and 2009. We also determined the source areas of the EC and LAS measurements with a footprint model for each site and discussed the differences between the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
295
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(306 citation statements)
references
References 52 publications
10
295
0
1
Order By: Relevance
“…For instance, Wilson et al (2002) also recorded an annual mean EBR of 0.84, ranging between 0.34 and 1.69 in an extensive study investigating 22 FLUXNET sites across the globe; EBR in ChinaFLUX sites ranged between 0.58 and 1.00, with a mean of 0.83 (Yuling et al, 2005); according to Were et al (2007), EBR values of about 0.90 were found over shrub and herbaceous patches in a dry valley in southeast Spain, whereas Chen et al (2009) showed a mean of 0.98 EBR for their study in the semi-arid region of Mongolia, and an EBR value of 0.80 was found by Xin and Liu (2010) in a maize crop in semi-arid conditions, in China. Using data from the Tibetan Observation and Research Platform (TORP), Liu et al (2011) observed an EBR value of 0.85 in an alfalfa field in semi-arid China. for the different seasons ranged between 0.70 and 1.12, with a mean of 0.92 ± 0.19.…”
Section: Surface Energy Balance Assessmentmentioning
confidence: 99%
“…For instance, Wilson et al (2002) also recorded an annual mean EBR of 0.84, ranging between 0.34 and 1.69 in an extensive study investigating 22 FLUXNET sites across the globe; EBR in ChinaFLUX sites ranged between 0.58 and 1.00, with a mean of 0.83 (Yuling et al, 2005); according to Were et al (2007), EBR values of about 0.90 were found over shrub and herbaceous patches in a dry valley in southeast Spain, whereas Chen et al (2009) showed a mean of 0.98 EBR for their study in the semi-arid region of Mongolia, and an EBR value of 0.80 was found by Xin and Liu (2010) in a maize crop in semi-arid conditions, in China. Using data from the Tibetan Observation and Research Platform (TORP), Liu et al (2011) observed an EBR value of 0.85 in an alfalfa field in semi-arid China. for the different seasons ranged between 0.70 and 1.12, with a mean of 0.92 ± 0.19.…”
Section: Surface Energy Balance Assessmentmentioning
confidence: 99%
“…The latter were collected from the Watershed Allied Telemetry Experimental Research (WATER) and provided by the Cold and Arid Regions Sciences Data Center at Lanzhou (available at http://westdc.westgis.ac.cn/ (accessed on 1 November 2014)) [63][64][65]. The ground measurements of latent heat flux with a time interval of 30-minute by the eddy covariance method at the towers were measured and processed.…”
Section: Eddy Covariance Flux Datamentioning
confidence: 99%
“…The borehole depths are 100 m for T1, 69 m for T2, 50 m for T3, 90 m for T4, and 20 m for T5 and T7. The HiWATER experiment Liu et al, 2011) provided the soil moisture data from 1 January to 31 December 2014 at the A'rou Sunny Slope station (100.52 • E, 38.09 • N).…”
Section: Study Area and Datamentioning
confidence: 99%